Cutaneous Adverse Events of Anti-PD-1 Therapy and BRAF Inhibitors - Gnanendran, Subashini Sharon; Turner, Lauren Maree; Miller, James Austin; Hwang, Shelley Ji Eun; Miller, Andrew Charles (Current treatment options in oncology, 2020)
Opinion statement The treatment of advanced melanoma has undergone a dramatic transformation over the last decade with the advent of targeted and immunomodulatory therapies. This transition from cytotoxic chemotherapy has yielded improvements in both survival and quality of life; yet despite their therapeutic advantages, these treatments have been associated with a diverse range of cutaneous adverse events (AEs). These range from relatively benign eczematous conditions to more severe inflammatory and bullous disorders, and can include induction of second malignancies. AEs can result in serious morbidity and risk of mortality if not recognised and managed early. As a consequence of their novelty, and rapid uptake, these agents have been subject to intense scrutiny and there is a general understanding that cutaneous AEs should be anticipated in treatment plans. Dermatologists should be integrated into management teams to assist in the development of treatment protocols for anticipated common AEs and to provide expert management of more severe, rare or unusual AEs. Our experience has shown a reduction in treatment interruptions, more rapid recognition of unusual AEs and improved management pathways for patients suffering cutaneous AEs.